2014
DOI: 10.1016/j.ejcdt.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the histopathological prototypes of the pleural fluid and granulomatous tissue reaction associated with pleural tuberculosis

Abstract: Purpose: The aim of this study is to differentiate between the histopathological features of pleural tuberculosis both free and encysted forms of pleural effusion as regards pleural fluid cytology and pleural tissue granulomatous tissue reaction and assess the effects of combined microbial infection on histopathological and clinical residuals.Patients and methods: One hundred and ninety patients were confirmed to be tuberculous by pleural tissue biopsy. Pleural fluid cytopathology and TB granulomatous tissue b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Generally, a frankly hemorrhagic or even serosanguinous fluid is unlikely to be tuberculous [ 20 , 21 ]. Our study had only two such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a frankly hemorrhagic or even serosanguinous fluid is unlikely to be tuberculous [ 20 , 21 ]. Our study had only two such cases.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, positivity was reported in 10% of cases. 4 Culture of pleural biopsy is helpful and is positive in 85% of cases. In our study, material for culture was available in 5 cases and in all the cases culture was positive.…”
Section: Discussionmentioning
confidence: 99%